[tex]a=\frac{5}{9}\cdot \frac{9}{25}-\frac{2}{25}\cdot \frac{25}{10}\\\\ a=\frac{1}{5}-\frac{1}{5} \\\\ a=0[/tex]
[tex]b=\frac{3}{2}\cdot (\frac{29}{9}-\frac{10}{3})^2 +\frac{75}{90} \\\\b=\frac{3}{2}\cdot \frac{1}{81} +\frac{75}{90} \\\\b=\frac{1}{54}+\frac{15}{18} \\\\b=\frac{46}{54}\\\\ b=\frac{23}{27}=0,(851)[/tex]
[tex]c=\frac{1}{5}- \frac{1}{5} \cdot (\frac{3}{4} -\frac{1}{4})\\\\ c=\frac{1}{5} -\frac{1}{5} \cdot \frac{1}{2}\\\\ c=\frac{1}{5} -\frac{1}{10} \\\\c=\frac{1}{10}=0,1[/tex]
Le ordonam crescator:
b>c>a
Un alt exercitiu gasesti aici: https://brainly.ro/tema/9959930
#SPJ1